Czasowniki współczesnego śląskiego języka literackiego (płaszczyzna semantyczna, etymologiczna i morfologiczna) - Jaroszewicz, Henryk (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The article provides the characteristics and classification of the most frequentative verbs and verb phrases used in contemporary Silesian literature. It has been established that the largest number of the studied forms is related to the different ways people physically influence the reality that surrounds them and mental processes (i.e. cognitive, evaluative and descriptive ones). The lexical diversity between Polish standard lexis and Silesian literary usage amounts to fifty-eight percent. What influences this diversity is the presence of words of German and Czech origin which amount to almost a tenth of the Silesian lexicon. Slightly less than half of the verbs are derived forms, in the vast majority formed through prefixation, aspect suffixation and postfixation. The semantic and morphological structure of the studied verb forms demonstrates a farreaching intellectualisation and formal complexity of the Silesian lexicon.